2016
DOI: 10.3389/fpls.2016.00082
|View full text |Cite
|
Sign up to set email alerts
|

Combining Drought Survival via Summer Dormancy and Annual Biomass Productivity in Dactylis glomerata L.

Abstract: Under Mediterranean climates, the best strategy to produce rain-fed fodder crops is to develop perennial drought resistant varieties. Summer dormancy present in native germplasm has been shown to confer a high level of survival under severe drought. Nevertheless it has also been shown to be negatively correlated with annual biomass productivity. The aim of this study was to analyze the correlations between summer dormancy and annual biomass productivity related traits and to identify quantitative trait loci (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The low forage productivity of many summer-dormant populations is a disincentive to adoption of cultivars with this trait, even though the superior persistence of these plants provides some compensation to this drawback. In this context, the recent publication of research exploring the possibility of breaking this trade-off is timely (Kallida et al 2016). Even though these researchers observed that high summer dormancy was negatively correlated with annual biomass production (−0.34, P < 0.005), they did note that some progeny had both high dormancy and high productivity indicating the potential to break this trade-off.…”
Section: Summer Dormancy To Improve Survival Of Extended Extreme Dromentioning
confidence: 99%
“…The low forage productivity of many summer-dormant populations is a disincentive to adoption of cultivars with this trait, even though the superior persistence of these plants provides some compensation to this drawback. In this context, the recent publication of research exploring the possibility of breaking this trade-off is timely (Kallida et al 2016). Even though these researchers observed that high summer dormancy was negatively correlated with annual biomass production (−0.34, P < 0.005), they did note that some progeny had both high dormancy and high productivity indicating the potential to break this trade-off.…”
Section: Summer Dormancy To Improve Survival Of Extended Extreme Dromentioning
confidence: 99%
“…Such pseudo F 1 / F 2 populations have been genotyped and phenotyped to identify QTL for several agronomical and physiological traits in L. perenne ( Muylle et al , 2005 ; Barre et al , 2009 ), L. multiflorum ( Studer et al , 2007 ), F. pratensis ( Ergon et al , 2006 ; Alm et al , 2011 ), tall fescue ( Festuca arundinacea ) ( Saha et al , 2009 ) and cock’s-foot ( Dactylis glomerata ) ( Kallida et al , 2016 ; Zhao et al , 2016 ). Because single F 1 plants cannot be selfed, pseudo-test crosses or full-sib matings of F 1 plants have been widely employed to construct pseudo-backcross or pseudo- F 2 populations.…”
Section: Practical Applications Of Sc In Forage Grassesmentioning
confidence: 99%
“…This in general might be true as pleiotropy is the predominant cause of trait association over linkage 31 . A negative correlation between summer dormancy and vegetative productivity was observed by Shaimi et al 28 and Kallida et al 27 , however they described the correlation as environmental adaptation rather than genetic control.…”
Section: Resultsmentioning
confidence: 88%
“…Thus, transgressive segregation in a population is highly likely which is useful for QTL mapping 26 . In summer dormancy related traits, it was reported in D. glomerata 27,28 . In this study, we find that summer dormancy is not only imbedded in the 103-2, but the Continental parent also contributes alleles.…”
Section: Resultsmentioning
confidence: 98%